2011
DOI: 10.1093/nar/gkq1340
|View full text |Cite
|
Sign up to set email alerts
|

hSSB1 interacts directly with the MRN complex stimulating its recruitment to DNA double-strand breaks and its endo-nuclease activity

Abstract: hSSB1 is a recently discovered single-stranded DNA binding protein that is essential for efficient repair of DNA double-strand breaks (DSBs) by the homologous recombination pathway. hSSB1 is required for the efficient recruitment of the MRN complex to sites of DSBs and for the efficient initiation of ATM dependent signalling. Here we explore the interplay between hSSB1 and MRN. We demonstrate that hSSB1 binds directly to NBS1, a component of the MRN complex, in a DNA damage independent manner. Consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
119
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(122 citation statements)
references
References 29 publications
2
119
1
Order By: Relevance
“…In mammalian cells, the OB-fold proteins RPA and hSSB1 have been predicted to be the homologs of bacterial ssDNA binding protein (17). However, it has been shown that the functions of hSSB1 and RPA in DNA damage may be distinct (17,18,21,22,24). Unlike RPA or other known OB-fold proteins, the affinity of hSSB1 for ssDNA is relatively low.…”
Section: Ints3mentioning
confidence: 99%
See 3 more Smart Citations
“…In mammalian cells, the OB-fold proteins RPA and hSSB1 have been predicted to be the homologs of bacterial ssDNA binding protein (17). However, it has been shown that the functions of hSSB1 and RPA in DNA damage may be distinct (17,18,21,22,24). Unlike RPA or other known OB-fold proteins, the affinity of hSSB1 for ssDNA is relatively low.…”
Section: Ints3mentioning
confidence: 99%
“…More recent studies have shown that hSSB1 is not only rapidly recruited to DSBs, but also interacts with the MRN complex, and may facilitate its recruitment to the DNA damage sites (18,19). This interaction indicates that hSSB1 is likely one of the earliest DNA damage repair proteins recruited to DNA damage sites.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, the SOSS complex (INTS3-hSSB1-C9orf80) has been shown to play key roles in DNA damage response and DNA repair [22][23][24][25]. Mechanistically, hSSB1 has recently been shown to (1) be required for the efficient recruitment of the MRN complex, (2) bind directly with NBS1 and (3) stimulate the endonuclease activity of the MRN complex [26,27]. Moreover, we have recently shown that hSSB1 regulates cell cycle progression and DNA damage checkpoints by modulating the stability of p21 in cancer cells [28].…”
Section: Introductionmentioning
confidence: 99%